Naše zkušenosti s náhradou I. MTP kloubu palce implantátem ToeFit Plus - Barták, Vladislav; Popelka, Stanislav; Hromádka, Rastislav; Pech, Jan; Jahoda, David; Sosna, Antonín (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2010)
PURPOSE OF THE STUDY: Hallux rigidus is a frequent disease of the first metatarsophalangeal (MTP) joint. It is a painful condition markedly reducing joint motion. For grade-3 and grade-4 disease, as classified by Coughlin, first MTP joint replacement is another option of surgical treatment, in addition to resection arthroplasty or arthrodesis. MATERIAL AND METHODS: In a group of 27 patients with symptomatic hallux rigidus, 28 MTP joint replacements using a TOEFIT-PLUS implant were carried out in the 2005-2009 period. There were 24 women and three men, with an average age of 56.3 years. The average follow-up was 24 months (range, 4 to 48). Indication for surgery included hallux rigidus in 20, conditions following Keller's arthroplasty in five, necrosis of the first metatarsus head in two cases and a condition after the Austin procedure in one patient. Pain, assessed by the Kitaoka score, and the range of joint motion; were evaluated before the surgery and at the final follow-up visit this also included the radiographic assessment of implant position and its integration. RESULTS: Of the 28 implants used, nine were hemiprosthetic and 19 total joint replacements. The average time between surgery and full weight-bearing was 6.6 weeks (range, 5 to 8) in both groups. The post-operative Kitaoka score was 87.1 (68-100) as compared with the preoperative value of 36.3 (24-52), and this difference was statistically significant.The range of motion at the first MTP improved from 14.7 degrees pre-operatively to 38.5 degrees post-operatively. There was no statistically significant difference in joint function, as assessed by the Kitaoka score and range of motion, between the two groups (hemiprosthetic vs. total joint replacements). The complications included prolonged skin healing with minor dehiscence in four cases. Revision surgery was required in three cases because of restricted joint motion associated with pain. In three cases of the total joint replacement group, there was radiographic evidence of asymptomatic osteolysis around both the phalangeal and the metatarsal component. In the hemiarthroplasty group, no osteolysis was recorded. DISCUSSION: Up to now several types of implants have been developed to alleviate pain and restore and maintain the first MTP motion in patients with hallux rigidus.The TOEFIT-PLUS implant belongs to the most recent ones. Our results are in agreement with those of other currently used replacements in terms of clinical and functional evaluation. The complications recorded in our study are also similar to those reported in the literature, which include aseptic loosening, dislocation and mechanical failure of the implant. There is no consistent approach to their treatment. Arthrodesis with tricortical graft seems to be an option, but it carries a considerable risk of failure. Since in our patients aseptic loosening was recorded only in the total joint replacement group, hemiarthroplasty has recently been preferred, because it has clinical and functional outcomes as good as total joint replacement. CONCLUSIONS: Our results with the use of TOEFIT-PLUS replacement show that this implant is effective in the treatment of hallux rigidus advanced stages and has good clinical outcomes, i.e., maintenance of motion at the MTP joint of the big toe, pain alleviation and early weight bearing. Since hemiarthroplasty is associated with fewer complications whose potential treatment is easier, this approach seems to have a better prospect than total joint replacement.
Keywords: Male; Adult; Aged; dospělí; mužské pohlaví; senioři; metatarzofalangeální kloub; artroplastiky kloubů; Arthroplasty, Replacement; Hallux Rigidus; lidé; ženské pohlaví; protézy kloubů; Humans; hallux rigidus; Joint Prosthesis; Metatarsophalangeal Joint; Female; lidé středního věku; Middle Aged